Strengthening Public Financial Management and Accountability - Muhakanizi, Keith (Ministry of Finance, Planning and Economic Development, 2014)
Allow me to welcome all of you to this year’s Budget Conference. This workshop is very important as it gives us an opportunity to appreciate current and emerging challenges and agree strategies to steer us forward towards achieving our national policy objectives in line with the Country’s Vision 2040.